2014
DOI: 10.1111/inr.12084
|View full text |Cite
|
Sign up to set email alerts
|

Smoking behaviours of adolescents, influenced by smoking of teachers, family and friends

Abstract: The Taiwanese government has regulated a comprehensive smoking ban in schools to prohibit both student and staff smoking on all school premises. To achieve this, schools should make tobacco control communication efforts. Nurses could address the combined influence of family and friends as well as the effect of school smoking restrictions to help prevent adolescents from smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
2
21
1
1
Order By: Relevance
“…Given that teachers are students' role models, it is particularly important that teachers do not smoke (5)(6)(7)(8)(9)26). The literature suggests that the TTM provides an effective way to quit smoking (11,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that teachers are students' role models, it is particularly important that teachers do not smoke (5)(6)(7)(8)(9)26). The literature suggests that the TTM provides an effective way to quit smoking (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, smoking prevention should be aimed at young people (5,6). Children and adolescents learn smoking from their role models (7).…”
Section: Introductionmentioning
confidence: 99%
“…31 Due to the social undesirability of cigarette smoking among girls in the EMR, 10,11 female teachers may avoid smoking at schools and thus they provide positive role models for their students against smoking. On the other hand, male teachers do not face the same social taboos, and smoke in front of their students, thereby affecting the student's smoking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the strong influence that friends have on smoking habits among adolescents. 10,33 Regarding alcohol consumption, those who consumed alcoholic beverages were six times more likely to be smokers. Several studies have demonstrated significant relationships between smoking and alcohol consumption among adolescents.…”
Section: 10mentioning
confidence: 99%